A Systemic Review on Robotic Versus Laparoscopic Adrenalectomy - Emad Rezkallah; Andrew Elsaify; Grace Lim; Wael Elsaify (New Visions in Science and Technology Vol. 5, 2021)
Background: Minimal invasive surgery has become the standard for most surgical procedures now. Many studies have tried to compare robotic versus laparoscopic to adrenalectomy. Objectives: The aim of this study is to review most of the available studies comparing robotic to laparoscopic adrenalectomy to evaluate which procedure provides the superior clinical outcomes. Methods: A systematic literature search of ScienceDirect and PubMed databases. The perioperative clinical outcomes were collected by two independent reviewers. We used Random-effects (DerSimonian-Laird) models to get the pooled effect estimates. Results: 18 studies were eligible in our study. 10 of them were prospective and 8 were retrospective. A total of 1376 patients underwent adrenalectomy, 592 (43.02%) were treated with RA and 784 (56.9%) with the LA technique. There were no significant differences between both groups regarding the conversion rate (Odds ratio: 0.70, 95% CI 0.31-1.57, P= 0.65), intraoperative complications (OR: 2.18, 95% CI 0.49- 9.71, P= 0.28), post-operative complications (OR: 0.83, 95% CI: 0.55-1.24, P= 0.49), and mortality (OR: 0.42, 95% CI: 0.07-2.72, P= 0.98). However, robotic adrenalectomy was associated with longer operative times (MD: 9.89 min, 95% CI: -2.79 to 22.58), shorter hospital stay (MD: -0.33, 95% CI: -0.46 to -0.21) with less blood loss (MD: -25.34, 95% CI: -36.77 to -13.91). Conclusions: We proved that robotic adrenalectomy has equal safety and feasibility with similar clinical outcomes when compared with laparoscopic approach. However, better well-designed studies are required to determine the role and cost-effectiveness of robotic adrenal surgery.